2016
DOI: 10.1590/1983-40632016v4641371
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of black common bean genetic breeding in Brazil

Abstract: The increase in grain yield and other agronomic traits, in common bean cultivars, is due, in large part, to its genetic breeding. This study aimed at estimating the genetic progress for grain yield and other important agronomic traits in black common bean cultivars recommended by Brazilian breeding programs between 1960 and 2013. A randomized blocks design was used, with three replications and 40 black common bean cultivars. The following traits were evaluated: grain yield and appearance, plant architecture, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The black group accounts for only 17% of the Brazilian production (Faria et al, 2014), therefore, less breeding efforts are invested than for the carioca group. However, since 1988, significant progress was observed in the genetic gain of black bean cultivars, and cultivars that reach higher yield levels are still being developed (Barili et al, 2016).…”
Section: Traits With H Gmentioning
confidence: 99%
“…The black group accounts for only 17% of the Brazilian production (Faria et al, 2014), therefore, less breeding efforts are invested than for the carioca group. However, since 1988, significant progress was observed in the genetic gain of black bean cultivars, and cultivars that reach higher yield levels are still being developed (Barili et al, 2016).…”
Section: Traits With H Gmentioning
confidence: 99%
“…According to RAMALHO et al (2012), the increase in grain yield in the bean crop in the country observed in the last decades reflect a continuous action of the Brazilian research institutes in activities (2014), andBARILI et al (2016) show genetic gains ranging between 1.07% and 3.26% per year. It should be emphasized that, unlike the studies carried out by MATOS et al (2007), CHIORATO et al (2010), FARIA et al (2014 and BARILI et al (2016), the use of QR made it possible to obtain information about the effect of the adaptability parameter throughout the grain yield distribution; and therefore, how it changed over the last 50 years of genetic improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the large number of cultivars recommended for cultivation in different regions of Brazil, the high demand for more productive cultivars may lead to the loss of some traits, and/or not include other characteristics of interest in the bean production chain (Faria et al, 2014). Among these, the technological quality of the grains is distinctive.…”
Section: Introductionmentioning
confidence: 99%